Short-term changes in the mental health of recently enrolled university students - Rubi Abigail Cruz-Sanchez; Luis Enrique Ferrer-Juárez; Martha Edith Reyes-Garduño; María José Gil-Trejo; Sergio Manuel Sánchez-Moguel; Sofía González-Salinas (Journal of Mental Health and Human Behaviour, 2019)
Background: There are no studies that evaluate whether briefly after beginning of university studies, emotional changes, sleeping alterations, or disordered eating habits take place. Aim: To evaluate whether depression, anxiety, stress, sleep quality, and eating behaviors change 1 month after the beginning of medical school. Methods: We applied an online version of the scales Depression, Anxiety, and Stress Scale-21, Pittsburgh Quality Index, and Eating Attitudes Test-26 to recently enrolled medical students in their 1st week of classes and 1 month after. A total of 17 students completed both tests; their mean age was 18.4 years. Results: Sleep quality decreased 1 month after starting undergraduate studies, while no significant changes occurred in the level of depression, anxiety, stress, or eating behaviors. Importantly, waist circumference increased 1 month after starting classes. A correlation analysis showed that poor sleep quality in Test 2 was positively related to depression, anxiety, and stress also in Test 2. By multivariate linear regression, we found that sleep quality was only statistically related to depression scores. We found no statistical relationship between eating behaviors and the emotional state of the students. Conclusion: We provide evidence in favor of a relationship of emotional alterations and sleep quality while did not find an association of these variables with eating behaviors. We conclude that briefly after enrollment at medical school, sleep quality is mainly affected and this may later lead to emotional alterations.